ANALISIS DAMPAK KUALITAS ASET PRODUKTIF DAN LIABILITAS TERHADAP KINERJA PERBANKAN SYARIAH DI INDONESIA PADA MASA PANDEMI COVID-19 - Hidayah, Poppy; Fahreza, Muhammad Rahul (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2021)
Financial banking affected by the Covid 19 pandemic. Banking in Indonesia adheres to a dual banking system consisting of conventional banking and sharia banking, Islamic banks such as BRI sharia, Mandiri sharia, etc. in 2021 to switch to Indonesian sharia banks, as a result of Covid 19 it is possible for banks not to carry out operational activities as well as in the form of sharia and conventional. asset and liability management, namely spread management which is related to the maintenance of positive spreads, between interest rates on an interest earning post between several aspects of assets and financing on aspects of balance sheet liabilities. The purpose of this study was to evaluate the magnitude of the quality of earning assets and liabilities that had an impact on the performance of Islamic banking in Indonesia during the COVID-19 pandemic. The primary data in this study was secondary data obtained from several financial performance reports at BRI Syariah banks and Indonesian Islamic banks published in March 2020 - September 2021. The results of the study using the F test show that the quality of earning assets and liabilities has a positive and significant impact on the high and low performance of Islamic banking.